Feasibility of structured endurance training and Mediterranean diet in BRCA1 and BRCA2 mutation carriers - an interventional randomized controlled multicenter trial (LIBRE-1) - Kiechle, Marion; Dukatz, Ricarda; Yahiaoui-Doktor, Maryam; Berling, Anika; Basrai, Maryam; Staiger, Vera; Niederberger, Uwe; Marter, Nicole; Lammert, Jacqueline; Grill, Sabine; Pfeifer, Katharina; Rhiem, Kerstin; et al. (BMC Cancer, 2017)
Background: Women with pathogenic BRCA germline mutations have an increased risk for breast and ovarian cancer that seems to be modified by life-style factors. Though, randomized trials investigating the impact of lifestyle interventions on cancer prevention and prognosis in BRCA carriers are still missing. Methods: We implemented a multicenter, prospective randomized controlled trial in BRCA1/2 patients, comparing a lifestyle intervention group (IG) with a control group (CG) with the primary aim to prove feasibility. Intervention comprised a structured, individualized endurance training alongside nutrition education based on the Mediterranean diet (MD) for 3 months, plus monthly group training and regular telephone contact during the subsequent 9 months. The CG attended one session on healthy nutrition and the benefits of physical activity. Primary endpoints were feasibility, acceptance and satisfaction over 12 months. Furthermore, effects on physical fitness, diet profile, body mass index (BMI), quality of life and perceived stress were investigated. Results: Sixty-eight participants (mean age 41, mean BMI 23.2 kg/m2) were enrolled, of whom 55 (81%, 26 IG, 29 CG) completed 12 months. 73% (n = 26) participated in at least 70% of all intervention sessions. Predictors for drop-outs (19%; n = 13) or non-adherence (27%; n = 7) were not found. 73% rated the program highly and 80% would participate again. Severe adverse events did not occur. Positive effects in the IG compared to the CG were observed for secondary endpoints: BMI, MD eating pattern and stress levels. Conclusions: This lifestyle intervention was feasible, safe and well accepted. Positive results on eating habits, physical fitness and stress levels warrant a larger randomized trial. Trial registration: The study has been retrospectively registered at ClinicalTrials.gov (reference: NCT02087592 ) on March 12, 2014. The first patient was included on February 24, 2014.
CRIS-Team Scopus Importer:2023-03-08
Keywords: BRCA1; BRCA2; Exercise; Hereditary breast cancer; Hereditary ovarian cancer; Mediterranean diet; Psychological support